Мягкая игрушка: веселая компания / Н. Белова - Белова Наталья Руфиновна (Академия "Умелые руки", 2002)
Экземпляры: ф.8 (20221205) / Инвентарный номер: 62844 / Цена: / Сис.шифр: 37.248 / Авт.знак: Б 43 / ГРНТИ: 75.35 / ББК: 37.248